HUBUNGAN PROSES REKRUTMEN DAN SELEKSI PEGAWAI DENGAN KINERJA PEGAWAI UNIT ADMINISTRASI DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2025 - Rizqi Nanda Putri; Lina Febriani Tanjung; Nanda Aginta Ginting (Jurnal Inovasi Kesehatan Masyarakat, 2026)
Employee performance is a crucial indicator of organizational success, especially in the healthcare sector such as hospitals. One key factor influencing performance is the recruitment and selection process. This study aimed to examine the relationship between recruitment and selection process and the performance of administrative staff at Sembiring General Hospital Deli Tua in 2025. A quantitative method with a cross-sectional design was applied. The study involved a total sample of 61 respondents, representing the entire administrative staff, selected using a total sampling technique. Data were collected by using a structured closed-ended questionnaire and the data analyzed with the chi-square statistical test. The results revealed a significant relationship between the recruitment process and employee performance (p = 0.000 < 0,05), while no significant relationship was found between the selection process and employee performance (p = 0.104 > 0,05). These findings suggested that a transparent, objective, and structured recruitment process contributes significantly to performance improvement. In contrast, a rushed selection process without clear evaluation indicators may hinder the achievement of optimal performance. The issue was evident at the hospital, where the selection process was carried out hastily to fill vacancies without comprehensive candidate assessment. There fore, it is recommended that hospital management improve the selection system by clarifying evaluation criteria and strengthening the integration between recruitment and selection processes. Proper planning in both stages is essential to produce competent, loyal, and high-performing human resources capable of delivering excellent administrative services. Are expected to serve as a reference for improving HR management policies and as a foundation for future research exploring deeper connections between recruitment, selection, and employe performance in healthcare institutions.